A descriptive study of the temperature at which anaesthetic refrigerated drugs are stored in operating theatre suites at Universitas Academic Hospital - Cloete, Nadia Danielle (University of the Free State, 2020)
Background: Temperature sensitive anaesthetic drugs require storage within individual theatre suites in order to be easily accessible to the anaesthetist for immediate use. This easy accessibility of drugs poses a risk of drug degradation due to incorrect temperature storage range. The method of storing refrigerated anaesthetic drugs in theatre suites, within a cooler box with a frozen eutectic gel pack (referred to as a cold drug storage unit) is well recognised and practiced. Yet, this method is poorly supported by literature and ill-defined in practice guidelines. The aim of this study is to determine whether refrigerated drugs in the operating theatre suites at Universitas Academic Hospital (UAH), during working weekdays, are stored according to the manufacturer’s temperature storage recommendation. Method: A descriptive observational study was done on the cold drug storage units in nine theatres suites at Universitas Academic Hospital, at six fixed time slots from 07:30 to 17:00, on five consecutive weekdays. The cold drug storage unit temperatures were measured and was assessed for adequacy of storage of refrigerated anaesthetic drugs according to the manufacturer’s recommendation on the package leaflet. The factors that could influence the internal environment of the cooler box were investigated; theatre room temperature, storage method of drugs within the cold drug storage unit, number, size and placement of the gel packs, the number of ampoules/vials and the utilisation of the operating theatre. Results: Five hundred and forty five temperature measurements were taken of which 268 were theatre room temperature with an accompanying 267 cold drug storage unit temperature measurements and ten main storage refrigerator temperature measurements. The cold drug storage unit temperature, for all theatres for the five days, was in the range of 4,30C – 23,80C with a median of 14,80C. This method of drug storage was not conducive to store all temperature sensitive anaesthetic drugs (requiring storage at 20C – 80C) on 235 temperature measurement (88%with a 95% Confidence Interval of 83,6% to 91,4%). The statistically significant factor (p <0,001) determining the cold drug storage unit temperature to fulfil the manufacturers recommendation to maintain temperatures below 80C was the number, size and placement of the eutectic gel packs within the cold drug storage unit. With the use of two eutectic gel packs, placed above and below the drugs within a Styrofoam® cooler box, a desired temperature range of 20C – 80C can be maintained for an average of 4 hours and 30 minutes, to a maximum time frame of 9 hours and 30 minutes, in a theatre suite with a maximum room temperature of 25,70C. Conclusion: The current method of storing temperature sensitive drugs, in operating theatre suites at Universitas Academic Hospital does not fulfil the temperature storage requirements as set out by the drug manufacturer’s most of the time. This method of passive refrigeration should not be abandoned as this study highlights the potential to maintain temperature below 80C...This potential success demonstrated in the study can be utilised to further research in determining the optimal storage conditions to store temperature sensitive anaesthetic drugs in an operating theatre suite within a resource limited environment.
Dissertation (M.Med (Anaesthesiology))--University of the Free State, 2020
Keywords: Secure anaesthetic drug storage; Temperature sensitive medication storage; Anaesthetic drugs for balanced anaesthesia; Anaesthetic drug stability; Drug degradation products; Cold chain medicines; Drug manufacturer’s storage recommendations; Passive refrigeration; Cold drug storage unit; Cooler Box with a eutectic gel pack; Serial temperature measurements